Government Spending and Growth Cycles: Fiscal Policy in a Dynamic Context - Jamee K. Moudud (Levy Economics Institute of Bard College, 1998)
In this paper the impact of fiscal policy is analyzed within the context of an endogenous growth and cycles model. The investigation shows the different situations in which government expenditure can lead to both crowding-in and crowding-out of output and employment. With regard to the cycle, an increase in the share of government spending leads to an expansion of output, which is given a greater stimulus with a higher degree of monetization. Expansionary monetary policies accompanying the fiscal expansion tend to make the upswing longer and the downswing more shallow, i.e., the cycle becomes more asymmetric. The medium-run dynamics of the model along its warranted growth path essentially rest on the relative movements of business retained earnings (i.e., the private savings rate since household savings are ignored) and the government spending share. With the private savings rate fixed, a rise in the government spending share leads to medium-run crowding-out. On the other hand, if policies such as investment tax credits, lower rates of corporate taxation, and accelerated deductions for capital depreciation stimulate the growth of the business retained earnings, then an increase in the government spending share may either not have any effect on the warranted path or may even raise it, i.e., there might be crowding-in. Moreover, abstracting from any changes in retained earnings, an increase in the level of government spending produces an expansionary cyclical effect with no medium-run crowding-out. Finally, the model exploits the empirical finding that infrastructure investment by the government lowers business costs. This relationship is used to demonstrate that the warranted growth path can be increased via a shift from government consumption expenditures to infrastructure investment. In contrast to mainstream analyses these complex results imply that, within limits, the state has a number of policy levers at its disposal to regulate output and employment.
Keywords: 330